Desain Sistem Manajemen Aset untuk Jaringan Irigasi Tersier - Heru Ernanda; Idah Andriyani; Indarto Indarto (Jurnal Irigasi, 2018)
This research presents the development of information system for irrigation asset management, called Sistem Informasi Management Asset Irigasi-Jaringan Tersier (SIMAI-JT).  The SIMAI-JT was designed as a management tool for tertiary irrigation network.  The development phase of SIMAI consists of system design, coding, and implementation.  The design phase includes structural and  functional design.  The program was designed and developed using VBA application over the GIS-platform. The input data was the spatial data in the form of points, polylines and polygons that describe the component of the irrigation network. The input data was acquired from the field survey (using camera and GPS) and digital conversion from the existing maps.  Furthermore, all the spatial data obtained were converted to GIS layers.  Then, the system integrated and display those layers in the form of photo, satellite imagery, and table information. Finally, an irrigation water user association at farmer level or Himpunan Petani Pemakai Air Irigasi (HIPPA) Sido Mulyo which located at Karangsono, District Bangsalsari, at the regency of Jember was selected to test the systems. The design was calibrated based on the capability and needs of HIPPA. The result shows that the information system must be designed with (i) showing maps according to the satellite imagery, identification and potential damage of tertiary irrigation network accompanied by the photo of the structure, (ii) artificial intelligence in determination of damage priority, and lastly (iii) institutional performances. The outcome of this program is being utilized in the meeting for planning institutional strategy in handling of tertiary irrigation network damage(s).